Impact of micrometastasis or isolated tumor cells on recurrence and survival in patients with early cervical cancer: SENTICOL Trial. Issue 3 (4th January 2019) - Guani, Benedetta; Dorez, Maxence; Magaud, Laurent; Buenerd, Annie; Lecuru, Fabrice; Mathevet, Patrice
Abstract : Objectives: The aim of this study was to evaluate the impact of micrometastasis and isolated tumor cells on disease recurrence in patients with early-stage cervical cancer. Methods: We included patients with International Federation of Gynecology and Obstetrics (FIGO) stage IA1 with lymphvascular space invasion, stage IA2, and IB1 who participated in the SENTICOL1 trial. A centralized histologic analysis with re-reading and ultrastaging was performed 3 months after surgery and treatment was not impacted by findings from our study. Patients were followed for 3 years and outcomes were compared according to prognostic factors. Results: A total of 139 patients were included and 13 recurrences were found. There were two recurrences in patients with positive sentinel lymph node (SLN) (one macrometastases and one micrometastases) and 11 recurrences in patients with negative lymph nodes (sentinel or non-sentinel). Among patients with positive SLN for micrometastases there was only one recurrence. No patient with isolated tumor cells on their lymph nodes experienced a recurrence. There was a significant decrease in disease-free survival in patients aged >50 years (p = 0.01). Conclusion: Evidence of micrometastasis or isolated tumor cells in the SLN of untreated patients with early cervical cancer in the SENTICOL1 trial did not impact progression-free survival.